1976
DOI: 10.1111/j.1744-7348.1976.tb01752.x
|View full text |Cite
|
Sign up to set email alerts
|

Ear and flag leaf photosynthesis of awned and awnless Triticum species

Abstract: The net photosynthetic rates of ears and flag leaves of awned and awnless wheats were measured by infra-red gas analysis in a controlled environment experiment. At 107 W m--2 the rates of net photosynthesis of the ears of two awned Triticum aestivum lines were two to three times greater than those of their isogenic awnless counterparts. The net rates of photosynthesis of the flag leaves of all four lines were, however, similar. Net photosynthetic rates of ears of T . durum and T . turgidum, which have much lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
2
13
0
Order By: Relevance
“…The contribution of awns to the total photosynthetic area of ears may be important. Thus differences in whole-ear area, as a consequence of differences in the total area of awns, accounts for the greater ear photosynthesis in barley than in bread wheat [15] and in tetraploid wheat than in hexaploid wheat [21]. Nevertheless, in Blum [5] net photosynthesis rates per unit area in the ear of the tetraploid wheat were only 25% of those of flag leaves.…”
Section: Some Implications For Breedingmentioning
confidence: 95%
“…The contribution of awns to the total photosynthetic area of ears may be important. Thus differences in whole-ear area, as a consequence of differences in the total area of awns, accounts for the greater ear photosynthesis in barley than in bread wheat [15] and in tetraploid wheat than in hexaploid wheat [21]. Nevertheless, in Blum [5] net photosynthesis rates per unit area in the ear of the tetraploid wheat were only 25% of those of flag leaves.…”
Section: Some Implications For Breedingmentioning
confidence: 95%
“…Jiang et al, 2006;Li et al, 2006;Olugbemi et al, 1976), their contribution to grain filling is not well known, and even controversial (e.g. McKenzie, 1972;see Tambussi et al, 2007 and references therein).…”
Section: Awn Photosynthesis and Contribution To Grain Fillingmentioning
confidence: 97%
“…Most of the previous studies have been focused on the awn phenotype ignoring the conferring locus. In general, research has centred on effects of the awn phenotype on grain yield and photosynthesis (Olugbemi et al, 1976;Weyhrich et al, 1994), largely ignoring potential effects on quality attributes. Two previous reports have indicated that awn phenotype is related to grain protein content (Ibrahim and Abo Elenein, 1977;Sharma et al, 1983).…”
Section: Introductionmentioning
confidence: 99%